Penyuluhan Tentang Turnover Perawat Covid 19 Dan Pemanfaatannya Dalam Pengambilan Kebijakan di Rumah Sakit Sembiring - Bahtera Bindavid Purba; Armanda - Prima; Afrilius Simanjuntak (INSTITUT KESEHATAN DELI HUSADA, 2021)
Hospitals must have quality human resources to be able to improve the quality of health services. Human resources are assets in an agency or company and are always needed in the process of producing goods and services. Nurses play an important role in the process of providing services in hospitals because they are directly involved with patients for 24 hours Nurses in hospitals are also a determining factor for service quality and hospital image, therefore nurses are required to always be professional in carrying out their duties by fostering a sense of care and concern. Must have empathy for the patient. Therefore, hospital management must pay more attention to nurses as part of human capital and not merely consider nurses as assets. If the company pays less attention to the existence of its employees and only pays attention to company profits, it will cause high turnover. Nursing care is the duty and responsibility of nurses in carrying out their professionalism and obtaining service rewards for the nurses' efforts in carrying out their duties as regulated in Law Number 38 of 2014. In fact, the turnover rate in private hospitals is higher than in government hospitals and teaching hospitals as well as nurses who work at the Sembiring Hospital, this is much influenced by the current condition, which is called the COVID 19 pandemic period, many nurses in the hospital were laid off due to breaking the chain of transmission of COVID-19. In this case, it is hoped that Hospitals need to make policies in dealing with the problem of nurse turnover in hospitals.